The Use of Attribute-Based Encryption for Secure Data Access: Penggunaan Enkripsi Berbasis Atribut untuk Akses Data yang Aman - Malath Sabri Kareem (Procedia of Engineering and Life Science, 2025)
General Background: Secure data sharing in cloud computing and Internet of Things environments requires advanced cryptographic mechanisms to ensure privacy and controlled access. Specific Background: Attribute-based encryption provides fine-grained access control, while blockchain technology introduces decentralized trust and data integrity. Knowledge Gap: Existing approaches often lack an integrated framework that combines encryption flexibility with decentralized security for scalable data sharing systems. Aims: This study aims to develop a secure data sharing framework by integrating attribute-based encryption with blockchain technology. Results: The findings indicate that the proposed approach enables fine-grained access control, strengthens data confidentiality, and supports secure and verifiable transactions in distributed environments. The framework also demonstrates improved reliability in managing encrypted data across multiple systems. Novelty: This study presents a combined architecture that integrates attribute-based encryption with blockchain to address limitations in traditional centralized security models. Implications: The results suggest that the proposed framework can support secure data sharing in cloud and IoT applications, offering a scalable solution for modern distributed systems. Keywords: Attribute Based Encryption, Blockchain Security, Data Sharing, Cloud Computing, Access Control Key Findings Highlights Fine grained policies regulate encrypted information access Distributed ledger supports transparent verification processes Integrated model enables secure multi environment communication